Oro-antral communication closure using collagenated porcine cortical lamina: A retrospective study of 34 cases - Jaballah-Magdeleine Nicolas; Boussouni Soufiane; Michel Philippe; Kati-Coulibaly Clotaire (EDP Sciences, 2024)
Introduction: Oro-antral communications (OAC) is a common complication in oral surgery. Many surgical techniques have been described, but traditional closure techniques have limitations, leading to the exploration of alternative approaches using resorbable biomaterials. This study aimed to assess the success of repairing OAC larger than 5 mm using collagenated porcine cortical lamina. Materials and methods: This retrospective study included 34 cases of OAC larger than 5 mm who underwent surgical repair using a porcine-derived collagenated cortico-cancellous plate, (Lamina Curve®). The median patient age was 46 yr. The study cohort consisted of 12 females and 22 males. The median follow-up time was 54 days. The primary outcome was the presence of complete mucosal closure, assessed at the 4th week postoperatively. Secondary outcomes included adverse events and stitching disunion. Results: Success rate was 97%. 9 patients (26.5% [12.1 ; 44]) had complications : 5 stitch disunions, 1 failure, 1 epistaxis, 1 infection and 1 nerve paresis. Of the 5 patients with stitch disunions (14.7% [4.12 ; 30.2]), all patients had complete mucosal closure at the primary outcome endpoint. Conclusion: Cortical lamina shows promising results in OAC repair. Success rates compare favorably with traditional flap-based methods. Further research is needed to validate these findings.